Security and Privacy From a Legal, Ethical, and Technical Perspective - Kalloniatis, Christos; Travieso-Gonzalez, Carlos (IntechOpen, 2020)
Understanding and realizing the security and privacy challenges for information systems is a very critical and demanding task for both software engineers and developers to design and implement reliable and trustworthy information systems. This book provides novel contributions and research efforts related to security and privacy by shedding light on the legal, ethical, and technical aspects of security and privacy. This book consists of 12 chapters divided in three groups. The first contains works that discuss the ethical and legal aspects of security and privacy, the second contains works that focus more on the technical aspects of security and privacy, and the third contains works that show the applicability of various solutions in the aforementioned fields. This book is perfect for both experienced readers and young researchers that wish to read about the various aspects of security and privacy.